2010
DOI: 10.1088/0031-9155/55/13/n01
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid echo and x-ray image guidance for cardiac catheterization procedures by using a robotic arm: a feasibility study

Abstract: We present a feasibility study on hybrid echocardiography (echo) and x-ray image guidance for cardiac catheterization procedures. A self-tracked, remotely operated robotic arm with haptic feedback was developed that attached to a standard x-ray table. This was used to safely manipulate a three-dimensional (3D) trans-thoracic echo probe during simultaneous x-ray fluoroscopy and echo acquisitions. By a combination of calibration and tracking of the echo and x-ray systems, it was possible to register the 3D echo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Anatomical information from live 3D echo can also be combined with x-ray fluoroscopy for navigational purposes. 8,9 A review of these image fusion techniques can be found in Ref. 10.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical information from live 3D echo can also be combined with x-ray fluoroscopy for navigational purposes. 8,9 A review of these image fusion techniques can be found in Ref. 10.…”
Section: Introductionmentioning
confidence: 99%
“…Our method provides a framework for using echo data to estimate respiratory motion, which could be used in combination with a robotic arm (Ma et al, 2010) for automatic acquisition of the 3D live echo images during the procedure. In principle, the Bayesian model could be used without the measurement of the respiratory surrogate during the procedure, since the surrogate is optimised as part of the maximisation of the posterior probability.…”
Section: Discussionmentioning
confidence: 99%
“…One possible approach is to combine high spatial resolution images acquired in the pre-procedural phase, such as Magnetic Resonance Imaging (MRI) (De Buck et al, 2005;Rhode et al, 2005;Yu et al, 2005) or Computed Tomography (CT) (Sra et al, 2007;Knecht et al, 2008;Ector et al, 2008), with high temporal resolution X-ray fluoroscopy images acquired during the procedure. Interest in the use of echocardiography (echo) imaging as an intra-procedure modality has grown over the last few years (Grau et al, 2007;Linte et al, 2008;Wein et al, 2009;Ma et al, 2010;Noble et al, 2011;Gao et al, 2012) due to its high temporal resolution, non-invasive nature and low cost. However, echo images are affected by various artefacts and echo image quality strongly depends on the sonographer's experience and the subject's anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…Two approaches are possible: firstly, indirect registration via a registered CT or MR dataset [52,53] or direct registration via a tracked echo probe (Fig. 5) [54,55].…”
Section: Multimodal Data Fusionmentioning
confidence: 99%